Fundamentals of human neuropsychology. - Kolb, Bryan, 1947-; Whishaw, Ian Q., 1939- (New York : Worth, 2009)
Bryan Kolb and Ian Whishaw's Fundamentals of Human Neuropsychology was the first text to bring a comprehensive introduction to contemporary human neuropsychology to the undergraduate classroom. It gave students access to an extraordinary amount of cutting-edge research and made it coherent, relevant and understandable-with a presentation that reflected the authors' superb communication and teaching skills. That text returns in extensively updated new edition that keeps pace with the latest research while maintaining its trademark clarity and student-friendliness. And with its enhanced full-color art program, new case studies, and new companion Web site, the Sixth Edition provides both the most up-to-date understanding of the field and the most effective ways to teach and learn it.
Keywords: Neuropsychologie